The Effect of an Exercise Package for Students with Intellectual Disability on Motor and Social Development: Exercise package for students with Intellectual disability - Kashi, Ali; Dawes , Helen; Mansoubi , Maedeh; Sarlak, Zahra (Iranian Journal of Child Neurology, 2023)
Objectives Physical activity and reducing inactivity improve health, well-being and benefits the social development of young people with intellectual disability (ID) lasting into adulthood. Therefore, given the importance of encouraging an active lifestyle in adolescents, researchers developed and evaluated the feasibility and potential effect of a novel “Sport Science Research Institute (SSRI) exercise package for young people with intellectual disability” to improve the motor and social development of these individuals. Materials & Methods In a Randomised controlled trial between October 2019 to February-2020, Thirty-six 7-18-year-old students with mild intellectual disabilities who were studying in a special school in Tehran received the invitation to the study. Students were randomly divided into intervention (18 students) and control (18 students) groups. Before and after the exercise program, three sessions per week for 12 weeks, motor proficiency was measured using the Bruininks-Oseretsky Test of Motor Proficiency (BOT-2), and social development was measured using the Vineland Social Maturity Scale (VSMS). Results Pupils in the intervention group completed 92% of the sessions. The results of the ANCOVA test showed that the exercise program led to a statistically significant improvement in total motor proficiency (P<0.01) and total social maturity score (P<0.015). Conclusion According to this study the, SSRI training package achieved good adherence and increased physical activity and showed potential to improve motor and social skills in young people with intellectual disability.